Selfish-biased conditional cooperation: On the decline of contributions in repeated public goods experiments - Tibor Neugebauer; Javier Perote; Ulrich Schmidt; Malte Loos (Kiel Institute for the World Economy (IfW), 2007)
In the recent literature, several hypotheses have been put forward in order to explain the decline of contributions in repeated public good games. We present results of an experiment which allows to evaluate these hypotheses. The main characteristics of our experimental design are a variation of information feedback and an elicitation of individual beliefs about others' contributions. Altogether, our data support the hypothesis of conditional cooperation with a selfish bias.
Keywords: C72; C92; H41; 330; Information feedback; Public goods; Voluntary contributions; Conditional cooperation; Experimental economics; Öffentliches Gut; Nichtkooperatives Spiel; Wiederholte Spiele; Eigeninteresse; Experiment; Theorie